Analysis of Deformation Damage in Deep Well Roadway and Supporting Countermeasures - Jianjun Shi; Jicheng Feng; Rui Peng; Quanjie Zhu (Geotechnical and Geological Engineering, 2020)

Hybrid Partition-Based Patrolling Scheme for Maritime Area Patrol with Multiple Cooperative Unmanned Surface Vehicles - Jiajia Xie; Rui Zhou; Jun Luo; Yan Peng; Yuan Liu; Shaorong Xie; Huayan Pu (Journal of Marine Science and Engineering, 2020)
Multi-robot cooperative patrolling systems have been extensively employed in the civilian and military fields, including monitoring forest fires, marine search-and-rescue, and area patrol. Multi-robot area patrol problems refer to the activity that a team of robots works cooperatively and regularly to visit the key targets in the given area for security. Following consideration of the low cost and high safety of unmanned surface vehicles (USV), a team of USVs is organized to perform area patrol in a sophisticated maritime environment. In this paper, we establish a mathematical model considering the characteristics of the cooperative patrol task and the limited conditions of USVs. A hybrid partition-based patrolling scheme is proposed for a multi-USV system to visit targets with different importance levels in a maritime area. Firstly, a centralized area partition algorithm is utilized to partition the patrolling area according to the number of USVs. Secondly, a distributed path planning algorithm is applied to planning the patrolling path for each USV to visit the targets in a maritime environment to minimize the length of the patrolling path for the USV team. Finally, comparative experiments between the proposed scheme and other methods are carried out to validate the performance of the hybrid partition-based patrolling scheme. Simulation results and experimental analysis show the efficiency of the proposed hybrid partition-based patrolling scheme compared to several previous patrolling algorithms.

CD49a+CD49b+ NK cells induced by viral infection reflect an activated state of conventional NK cells - Wenhan Li; Jing Zhou; Xianwei Wang; Yuzhang Wu; Lilin Ye; Haiming Wei; Rui Sun; Zhigang Tian; Hui Peng (Science China Life Sciences, 2020)

Utilizing borehole electrical image and conventional logs to characterize petrology of mixed volcanic and sedimentary rocks in Jiamuhe Formation at JL2 Wellfield, Zhongguai Uplift, Junggar Basin, NW China - Rui Yuan; Lei Zhang; Qinghai Xu; Youlun Feng; Zhiyuan An; Jun Wu; Kang Zhao; Shuai Liu; Peng Huang (Arabian Journal of Geosciences, 2020)

Studies on support techniques for roadway bearing structure features under different geo-pressures - Rui Peng; Zhenhua Ouyang; Qifeng Zhao; Jianming Zhu (Arabian Journal of Geosciences, 2020)

Multi-AUVs Cooperative Target Search Based on Autonomous Cooperative Search Learning Algorithm - Yuan Liu; Min Wang; Zhou Su; Jun Luo; Shaorong Xie; Yan Peng; Huayan Pu; Jiajia Xie; Rui Zhou (Journal of Marine Science and Engineering, 2020)
As a new type of marine unmanned intelligent equipment, autonomous underwater vehicle (AUV) has been widely used in the field of ocean observation, maritime rescue, mine countermeasures, intelligence reconnaissance, etc. Especially in the underwater search mission, the technical advantages of AUV are particularly obvious. However, limited operational capability and sophisticated mission environments are also difficulties faced by AUV. To make better use of AUV in the search mission, we establish the DMACSS (distributed multi-AUVs collaborative search system) and propose the ACSLA (autonomous collaborative search learning algorithm) integrated into the DMACSS. Compared with the previous system, DMACSS adopts a distributed control structure to improve the system robustness and combines an information fusion mechanism and a time stamp mechanism, making each AUV in the system able to exchange and fuse information during the mission. ACSLA is an adaptive learning algorithm trained by the RL (Reinforcement learning) method with a tailored design of state information, reward function, and training framework, which can give the system optimal search path in real-time according to the environment. We test DMACSS and ACSLA in the simulation test. The test results demonstrate that the DMACSS runs stably, the search accuracy and efficiency of ACSLA outperform other search methods, thus better realizing the cooperation between AUVs, making the DMACSS find the target more accurately and faster.

Tree-ring-based temperature reconstruction since 1766 ce in the eastern Tianshan Mountains, arid Central Asia - Zhengbing Peng; Li Qin; Xinjian Li; Heli Zhang; Youping Chen; Rui Liu; Ruibo Zhang (Theoretical and Applied Climatology, 2020)

Mitigating Climate Change for Sugarcane Improvement: Role of Silicon in Alleviating Abiotic Stresses - Krishan K. Verma; Pratiksha Singh; Xiu-Peng Song; Mukesh Kumar Malviya; Rajesh Kumar Singh; Gan-Lin Chen; Sushil Solomon; Yang-Rui Li (Sugar Tech, 2020)

Infrared microthermometry of fluid inclusions in transparent to opaque minerals: challenges and new insights - Hong-Wei Peng; Hong-Rui Fan; M. Santosh; Fang-Fang Hu; Peng Jiang (Mineralium Deposita, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Low-frequency swell noise suppression based on U-Net - Rui-qi Zhang; Peng Song; Bao-hua Liu; Xiao-bo Zhang; Jun Tan; Zhi-hui Zou; Chuang Xie; Shao-wen Wang (Applied Geophysics, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Molecular Characterization and Promoter Analysis of Novel Sugar Transporter Gene ScERD6 in Sugarcane - Xiao-Rong Miao; Xu-Peng Zeng; Jun-Qi Niu; Aamir Mahmood; Li-Tao Yang; Bao-Qing Zhang; Yang-Rui Li (Sugar Tech, 2020)

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

The Environmental Functions and Ecological Effects of Organic Carbon in Silt - Rui Liu; Teng Ma; Wenkai Qiu; Ziqi Peng; Chenxuan Shi (Journal of Earth Science, 2020)

Transcriptome Profile Analysis of Resistance Inoculated by Dryopteris crassirhizoma Dryocrassin ABBA in Potato Tubers - Wenzhong Wang; Rui Gao; Tong Zhang; Lingling Chen; Peng Feng; Zongbao Zhao; Changxu Zhang; Fanxiang Min; Shuai Yang; Qi Wei; Mei Guo; Ying Chang (American Journal of Potato Research, 2020)

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Response Patterns of Biomarkers as Tools to Identify Toxic Effects of Cadmium and Lead on Bufo gargarizans Embryo - Rui Zheng; Minyao Wu; Hongyuan Wang; Jufang Peng (Bulletin of Environmental Contamination and Toxicology, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Optimization Analysis of Over-Sized Section Open-Off Cut Failure and Support - Jianjun Shi; Jicheng Feng; Peng Rui; Quanjie Zhu (Geotechnical and Geological Engineering, 2020)

Selective catalytic reduction of NOx by NH3 over CeVO4-CeO2 nanocomposite - Chao-peng Duan; Rui-tang Guo; Gui-lin Wu; Wei-guo Pan (Environmental Science and Pollution Research, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

In vitro and in vivo evaluation of the antifungal activity of fluoxetine combined with antifungals against Candida albicans biofilms and oral candidiasis - Liuliu Jiang; Linxia Zheng; K airui Sun; Peng Zhou; Rui Xu; Jingyi Gu; Xin Wei (Biofouling, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

First report of broad bean wilt virus 2 infection in eggplant in China - Peng-Huan Rui; Lei Jiang; Shuai Li; Xi-Zi Jiang; Qing-Qing Zhao; Ji Ying Feng; Tong Jiang (Journal of Plant Pathology, 2020)

Characteristics and dynamics of the Ganqiuchi rock avalanche triggered by a paleo-earthquake in the Northern Qinling Mountains - Ze-Hua Zhou; Yan Lyu; Sheng-rui Su; Shi-jie Liu; Hui Zhao; Peng Li; Yang Zhou (Journal of Mountain Science, 2020)

Release of tartrate as a major carboxylate by alfalfa (Medicago sativa L.) under phosphorus deficiency and the effect of soil nitrogen supply - Honghua He; Miaomiao Wu; Lei Guo; Chenbin Fan; Zekun Zhang; Rui Su; Qi Peng; Jiayin Pang; Hans Lambers (Plant and Soil, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Appropriate Dynamically-Reinforced Supporting Time Determination in Relation to the Time Effect of Stress Field Evolution: A Case Study on the Deep Soft-Rock Roadway in China - Li Cong; Ying-ming Li; Xiang-rui Meng; Chun-liang Dong; Guang-ming Zhao; Rui Peng; Ji-cheng Xu (Geotechnical and Geological Engineering, 2020)

Integration of hepatitis B virus DNA into p21-activated kinase 3 (PAK3) gene in HepG2.2.15 cells - Peng Ruan; Xiufang Dai; Jun Sun; Chunping He; Chao Huang; Rui Zhou; Isabelle Chemin (Virus Genes, 2020)

MiR-430 Can Affect the Mesoderm Formation and Metamorphosis of Paralichthys olivaceus by Targeting lefty Gene - Rui Li; Zhenwei Wang; Minmin Sun; Meiting Peng; Jie Qi; Zhigang Wang (Journal of Ocean University of China, 2020)

Mapping landslide susceptibility at the Three Gorges Reservoir, China, using gradient boosting decision tree, random forest and information value models - Tao Chen; Li Zhu; Rui-qing Niu; C John Trinder; Ling Peng; Tao Lei (Journal of Mountain Science, 2020)

Inhibition of methicillin-resistant Staphylococcus aureus (MRSA) biofilm by cationic poly (D, L-lactide-co-glycolide) nanoparticles - Yang Qiu; Yuqi Wu; Boyao Lu; Guanyin Zhu; Tao Gong; Rui Wang; Qiang Peng; Yuqing Li (Biofouling, 2020)

Anfibatide Preserves Blood–Brain Barrier Integrity by Inhibiting TLR4/RhoA/ROCK Pathway After Cerebral Ischemia/Reperfusion Injury in Rat - Peng Gong; Rui Li; Hui-Yu Jia; Zheng Ma; Xiao-Yi Li; Xiang-rong Dai; Sheng-Yong Luo (Journal of Molecular Neuroscience, 2020)

Biochar-related studies from 1999 to 2018: a bibliometrics-based review - Dongyang Li; Rui Zhao; Xing Peng; Zhifei Ma; Ying Zhao; Tiancheng Gong; Mengyang Sun; Yuxin Jiao; Tianxue Yang; Beidou Xi (Environmental Science and Pollution Research, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)